PERANCANGAN SISTEM E-KINERJA PEGAWAI : Berbasis Web Pada PT. Global Service management - Dandi Andrian (2021)
With various kinds of businesses that are within the scope of building a company, employees who work in their fields will greatly influence the progress of the company. One of them is by improving employee performance. With the aim of designing a performance information system, this is an effort to ensure that no one cooperates with the work of employees. This application system planning uses the Rapid Application Development (RAD) method. This application utilizes technology to support the company's vision, namely professionalism in providing services. In its application, employees will be made an application design, it aims to process data that will become a document. By using HTML and CSS on web pages along with the PHP programming language and server-based data using MySQL. It is hoped that this system can be useful in managing employees so that they can be effective and efficient.